Modified whale’s tail technique using amnion membrane for periodontal regeneration in the anterior teeth with diastema: A case report - Patil, Agraja Ganpat; Bhatt, Vaibhavi Hitesh (Indian Journal of Case Reports, 2019)
The biggest challenge during periodontal regeneration in the anterior region lies in the maintenance of esthetics. Whale’s tail technique has a novel flap design that achieves both these goals while maintaining the functional integrity of the periodontal tissues. A 46-yearold male reported with the chief complaint of bleeding from the gums. Periodontal examination of 11 shows probing pocket depth of 7 mm mesially with clinical attachment loss of 8 mm. Whale’s tail technique using demineralized freeze-dried bone allograft (DFDBA) and Amnion membrane was used in this case to achieve 4mm gain in clinical attachment level at the end of 11 months. This technique successfully demonstrates stable clinical outcomes in terms of management of anterior periodontal regeneration in diastema cases. Long term clinical trials are required to validate these results.